The scientist : the science library - Margenau, Henry; Bergamini, David (New York : Time-Life Books, 1976)
Discusses the scientist as a person and his role in modern life, describes various fields of science and explains the scientific method.
Includes bibliography and index.
Keywords: Science; Scientists